Advances in Xerogels: From Design to Applications - Caridi, Francesco; Paladini, Giuseppe; Fiorati, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The field of material science and engineering has witnessed a surge of interest in the development of novel xerogels-solid materials derived from gels-for a wide range of applications. Despite potential shrinkage, xerogels possess remarkable properties, including high porosity and a large surface area, owing to the interconnected network of pores formed during drying. Consequently, xerogels find valuable applications as catalysts, adsorbents, sensors, membranes, and drug delivery systems. The ability to conveniently control the structures and morphologies of xerogels during synthesis has garnered significant attention within the scientific community. In light of these considerations, this Special Issue of Gels compiles high-quality papers that showcase the latest advancements and breakthroughs in xerogel science, covering various aspects from design to application. Both theoretical and experimental cutting-edge studies exploring the structural, chemical, rheological, and dynamical properties of xerogels and their derivatives are included in this collection.